DEVIANT BEHAVIOR AS A SOCIAL, PSYCHOLOGICAL AND PEDAGOGICAL PROBLEM - Kalillayeva, U.A. (SCIENCE and SOCIETY, 2022)
The article is devoted to the increasingly urgent problem of children and adolescents’ deviant behavior, as well as of primary school children and, sometimes even preschool age.